Assessing nursing assistants' competency in palliative care: An evaluation tool. (November 2018) - Karacsony, Sara; Chang, Esther; Johnson, Amanda; Good, Anthony; Edenborough, Michel
Abstract: Nursing assistants are the largest aged care workforce providing direct care to older people in residential aged care facilities (RACF) in Australia and internationally. A palliative approach is a large component of this direct care that necessitates nursing assistants possess requisite knowledge, skills and attitudes. While training needs have been identified to enhance their practices, preservice education is variable, educational interventions have been adhoc and professional development found to be inadequate to the demands of the workplace. In addition, evaluation of nursing assistants' knowledge, skills and attitudes has lacked an instrument specifically tailored to nursing assistants' level of education and role responsibilities when providing a palliative approach. This paper reports on Phase 3 of a research study to develop such an instrument capable of assessing nursing assistants' knowledge of, skills in, and attitudes within a palliative approach. This phase assesses the usability and performance capabilities of the new instrument on a purposive sample of nursing assistants in two RACFs using the survey method. Results showed that the instrument was able to discriminate between groups of nursing assistants based on experience in role. Usability results indicated that the instrument is user friendly and time efficient.